Investigation of escherichia coli, escherichia coli O157:H7 and salmonella typhimurium in various exotic meats - Tan, Mei Chian (Universiti Malaysia Sarawak (UNIMAS), 2015)
Escherichia coli (E. coli) 0157:H7 and Salmonella typhimurium (s. typhimurium) are foodborne pathogens that cause food poisoning outbreaks since decades ago. Studies have shown that exotic meats have the potential to be contaminated by both pathogens. A total of 14 exotic meat samples namely wild boar (n=3), snake (n=3), soft-shelled turtle (n=3), frog (n=3), deer (n=l) and squirrel (n=l) were purchased and collected from wet markets, food court, restaurant and individuals for the present study. The isolation of E. coli and Salmonella spp. from the collected samples were accomplished through selective plating on EMBA and XLD agar respectively while polymerase chain reaction were used to detect the presence of E. coli 0157:H7 and S. typhimurium in the collected samples. The findings showed that 100% (14114) of the samples showed appearance of E. coli colonies on EMBA while 78.57% (11/14) of the samples showed appearance of Salmonella colonies on XLD agar. Both E. coli 0157:H7 and S. typhimurium were not detected from the collected samples through polymerase chain reaction. However, the results cannot prove that exotic meats are safe to be consumed. Hence, more related studies are required to further assess the microbial risk on consuming exotic meats and ensure food safety.